Students Mathematical Representation Ability in Learning Algebraic Expression using Realistic Mathematics Education - Yuhasriati Yuhasriati; Rahmah Johar; Cut Khairunnisak; Ulya Rohaizati; Al Jupri; Tuti Zubaidah (Universitas Syiah Kuala, 2022)
Mathematical representation ability (MRA) is crucial in solving mathematical problems, particularly in the topic of algebraic expressions. However, some students struggle to grasp algebraic forms in real-world circumstances. Learning through realistic mathematics education (RME) using context is one of the learning approaches that could help improve students' MRA. The objective of this study was to assess students' MRA in learningalgebraic expressionsthrough realistic mathematics education. This research employed mixed-method research with a sequential explanatory design. The subjects of this study were 27 seventh-grade students from a junior high school in Banda Aceh, Indonesia. Data on students' MRA were gathered through written test and task-based interviews. The descriptive analysis of written test data revealed that students' average score is 3.6, which is considered low compared to the maximum score of 8. The majority of students (n=24) satisfied the visual indicators of MRA as they successfully drew the composite shape. Whereas the most challenging MRA aspect for students to master was symbolic representation, only a few students (n=6) could solve the problem related to the multiplication of algebraic expressions. Students learning loss in the prerequisites due to online learning during the Covid-19 outbreak was one cause of the students' low performance on MRA.